Biomonitoramento citogenético, hematológico e bioquímico em agentes de endemias expostos à agrotóxicos no município de Valença - Piauí - Costa, Tacyana Pires de Carvalho (2014)
Insecticides based on organophosphates are widely used in eradication campaigns and high application of these products, without the use of biosecurity measures, contributes to the increased incidence of occupational poisoning in endemic agents. The study aimed to conduct a biomonitoring through biochemical, hematological and cytogenetic analyzes of agents of endemic occupationally exposed to organophosphate insecticides in the city of Valencia Piauí. The survey was conducted with 20 agents endemic and 20 non exposed workers. Applied a questionnaire recommended by the International Commission for Protection Against Environmental Mutagens and Carcinogens-ICPEMC, and biological material was collected for hematological, biochemical and cytogenetic analyzes. The population studied had a mean age of 44.15 years, working time of 14.75 years, weekly workload of 40 hours and 55% of agents said they use PPE. As for lifestyle 25% were smokers, 85% consumed alcohol and 30% report some underlying disease. Evaluating the hematological parameters no statistical significance when comparing the two groups. As biochemical variables for urea, creatinine, ALT, AST and BChE showed significant changes. In dosages of alkaline phosphatase and gamma glutamyl transferase, significant (p <0.01) compared to the unexposed group. Regarding the genotoxic analysis (cells with micronuclei), there was a statistically significant difference between the exposed groups (2.78) and unexposed (0.56). The nuclear changes were evidenced cariorrex (184.1 versus 717.0), karyolysis (138.5 versus 47.48), and binucleated cells (0.1413 versus 0.06087) of the exposed compared to the control group respectively. Although the numbers of karyorrhexis were more evident in the control group, and karyolysis binucleation parameters were genotoxicity along with micronuclei.